The Head Master Leadership Management In Improving Teacher Performance - Sutrisno, Sutrisno; Sholeh, Muh Ibnu; Jeffriansyah Dwisahputra Amori; Deny Gunawan Susandi; Pham Vu Phi Ho; Nur ‘Azah (Mudir : Jurnal Manajemen Pendidikan, 2024)
This research aims to gain an in-depth understanding of the leadership management of head master at MA Darunnajah Trenggalek. The main focus of the research is understanding Islamic-based leadership strategies, teacher empowerment, and responsiveness to the dynamics of contemporary Islamic education. This study used qualitative research methods. The data collection process involves in-depth interviews, participant observation, and document analysis, involving various participants, such as head master , teachers, and administrative staff. The research results show that Islamic-based leadership strategies have a positive impact on teacher performance at MA Darunnajah Trenggalek. Empowering teachers is the key to increasing their motivation and commitment, while responsiveness to the dynamics of contemporary Islamic education is found through curriculum updates and adaptive school policies. These findings contribute to the development of head master leadership practices in Islamic education environments. Practical implications include strengthening Islamic-based leadership strategies, increasing teacher empowerment, and developing responsive school policies. Recommendations include developing leadership training programs, aligning policies with Islamic values, and increasing collaboration with external parties. Thus, this research provides an in-depth view of leadership management at MA Darunnajah Trenggalek, providing a basis for developing policies and practices that are more effective in achieving the goals of Islamic education at the institution.